Environmental Hazards-Human and Policy Dimensions - Environmental Hazards-Human and Policy Dimensions (Taylor & Francis, 2026)
Environmental Hazards: Human and Policy Dimensions is an innovative, interdisciplinary and international research journal addressing the human and policy dimensions of hazards.
FI 0.61
Q3
Keywords: Biological; Earth & Environmental Food Science; Ciencia ambiental; Peligros ambientales; Acuerdos transformativos; Transformative agreements; Terremotos; Inundaciones; Tormentas